2018
DOI: 10.1038/s41531-018-0051-7
|View full text |Cite
|
Sign up to set email alerts
|

Viewpoint and practical recommendations from a movement disorder specialist panel on objective measurement in the clinical management of Parkinson’s disease

Abstract: Motor aspects of Parkinson’s disease, such as fluctuations and dyskinesia, can be reliably evaluated using a variety of “wearable” technologies, but practical guidance on objective measurement (OM) and the optimum use of these devices is lacking. Therefore, as a first step, a panel of movement disorder specialists met to provide guidance on how OM could be assessed and incorporated into clinical guidelines. A key aspect of the incorporation of OM into the management of Parkinson’s disease (PD) is defining cuto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
70
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 57 publications
0
70
0
3
Order By: Relevance
“…Moving these technologies from research interests to the routine clinical care armamentarium requires clinical validation and ongoing study of clinical utility. In recent years, early adopters have published consensus statements that define how COM data can augment clinical decision making as in the care of patients who are poor historians or have difficulty articulating symptoms, have excessive daytime sleepiness, and in the optimization of new therapies [30] [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moving these technologies from research interests to the routine clinical care armamentarium requires clinical validation and ongoing study of clinical utility. In recent years, early adopters have published consensus statements that define how COM data can augment clinical decision making as in the care of patients who are poor historians or have difficulty articulating symptoms, have excessive daytime sleepiness, and in the optimization of new therapies [30] [31].…”
Section: Discussionmentioning
confidence: 99%
“…In the management of diabetes mellitus and hypertension, managing patients to established targets is the standard of care. In the management of PD, these targets are starting to be defined by expert consensus [30] [31] though further studies are needed to demonstrate that treating PWP to particular targets will impact their clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that all the above‐mentioned data are derived from clinical outcomes scales, which provide us with only a snapshot of the patient condition, continuous monitoring technologies are set to add accuracy and objectivity to outcome‐based measures in value‐based healthcare systems. PD is not exempt and dyskinesias can be tracked using wearable sensors such as the Parkinson's KinetiGraph or Kinesia technology, both certified by the recognized regulatory bodies with a CE mark to provide some assurance regarding safety, efficacy, and privacy . Illustrating this are data from an unselected cohort of 200 PD patients being recruited to an international wearable sensor registry study showing that significant dyskinesia is observed among only 18.5% of the moderate‐ to advanced‐stage PD population referred to King's College Hospital (London), a major academic teaching hospital.…”
mentioning
confidence: 99%
“…They have shown promising results in research and clinical trials to objectively measure and monitor symptoms, both on-site and remotely [17,28,29,30,31,32]. However, a limited number of commercial systems are available for such purposes [33] such as SENSE-PARK system [1] , Kinesia system [2] , Parkinson's Kinetigraph (PKG) [3] and Physilog [4] , and where they do exist, they show limited adoption and implementation [34] despite of the fact that these devices shows high reliability, validity and responsiveness [33,35], and have been used in the evaluation of PD symptoms and signs by individuals apart from development team and reported successful clinical trials [35,36]. Data from several studies suggest that these inconsistencies in adoption and implementation may be due to the lack of users' perspectives in devices design and development [37,38].…”
Section: Introductionmentioning
confidence: 99%